Analysis of Organizational Citizenship Behavior Based on Employee Engagement, Organizational Justice, and Work-Life Balance - chaniago, nicholas saputra; Arifin, Noor (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the influence of employee engagement, organizational justice and work-life balance on organizational citizenship behavior at the village hall office in Keling District. The population of this study is village hall employees in Keling sub-district. Methodology: the research design used is quatitative research. The population in this study is employees at the village hall office in Keling sub-district with a total of 113 people. The total population in this study is 113 people. The sampling technique used saturated samples, so that a sample of 113 people was obtained. The primary data needed is collected by survey by distributing a questionnaire using a google form to individuals or individuals. Result: The results of this study show that employee engagement has a significant positive effect on the organizational citizenship behavior of the village hall office in Keling District, organizational justice has a significant positive effect on the organization citizenship behavior of the village hall office in Keling Districtwork-life balance has a significant positive effect on the organization citizenship behavior of the village hall office in Keling District. Findings: This study highlights the importance of good employee engagement, high organizational equity, and maintaining a work-life balance that is conducive to achieving high organizational citizenship behavior. Novelty: This study describes the interaction between employee attachment, organizational justice, and work-life balance in the context  of organizational citizenship behavior in the organization of village hall offices. Originality: This study contributes to organizational citizenship behavior regarding the productivity of village hall office employees in Keca,atan Keling by overcoming the gap in understanding these variables. Conclusion Practical thinking is a recommendation for village hall office employees in Keling sub-district to develop strategies to improve organizational citizenship behavior in accordance with the expectations and goals of the organization. The population of this study is employees of the village hall office in Keling District.Type of Paper: Quantitative empirical research.